Dataset of SARS CoV-2 in wastewater in Örebro, Sweden - Malmberg, Maja; Myrmel, Mette; Khatri, Mamata (Swedish University of Agricultural Sciences, 2021)
This is a metadata record for a continuously updated dataset of SARS-CoV-2 RNA data in wastewater in Örebro, Sweden.

The dataset is part of a research study led by associate professor Maja Malmberg (SLU, Swedish University of Agricultural Sciences) and her research group in collaboration with associate professor Mette Myrmel (https://www.nmbu.no/emp/mette.myrmel) at the Norwegian University of Life Sciences.

The amount of SARS-CoV-2 virus is measured in wastewater from the wastewater treatment facility in Örebro. The research group is part of the Environmental Virus Profiling Research Area of the SciLifeLab National COVID-19 Research Program.

https://www.scilifelab.se/covid-19/national-program/environment/

After preparation, the viruses are extracted using ultra filtration and analyzed using qPCR technique for SARS CoV-2 RNA. RT-qPCR samples are normalized against Pepper Mild Mottle Virus (PMMoV).

From Oct 2020 until January 2021, three samples per week were taken and an average of the three values was calculated to provide a weekly estimate.

From February to March 2021, samples were only collected at one time point per week, and from April onwards two samples per week are analysed and the average presented. Primers used to detect the SARS-COV-2 gene have been previously used and verified by Corman and colleagues, 2020 (https://doi.org/10.2807/1560-7917.ES.2020.25.3.2000045) .

For more information see https://www.covid19dataportal.se/data_types/environment/wastewater/ The dataset started week 44 2020 and updates every second week.

The dataset is available as part of the Environmental Virus Profiling data section "The amount of SARS-CoV-2 virus in wastewater across Sweden" https://www.covid19dataportal.se/data_types/environment/wastewater/#orebro

on the Swedish COVID-19 Data Portal (https://covid19dataportal.se ).

Funded by the SciLifeLab/KAW National Covid-19 Research Program•https://www.scilifelab.se/covid-19/national-program
Keywords: Infectious diseases; Medical and Health Sciences; Medicin och hälsovetenskap; Infectious Medicine; Infektionsmedicin